2023
DOI: 10.1186/s12905-023-02185-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with fear of childbirth in a subsequent pregnancy: a nationwide case–control analysis in Finland

Abstract: Background Fear of childbirth can develop due to the concerns or adverse maternal or foetal outcomes experienced in a previous pregnancy. The aim of this study was to examine the main risk factors associated with the development of fear of childbirth during subsequent pregnancies and deliveries. Methods In this case–control study, data from the National Medical Birth Register were used to evaluate the events in previous pregnancies that were potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…A previous painful or uncomfortable birth experience might increase the desire for pain relief in subsequent pregnancies, which might increase the rate of pain relief, especially in multiparous women. According to a recent nationwide study in Finland, the most common factors in first pregnancy associated with FOC in subsequent pregnancies were instrumental vaginal deliveries, in‐labor CS, third‐ or fourth‐degree tear of the perineum, and shoulder dystocia 7 . All of these factors might increase the intensity of the pain and therefore increase the desire for pain relief in subsequent pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous painful or uncomfortable birth experience might increase the desire for pain relief in subsequent pregnancies, which might increase the rate of pain relief, especially in multiparous women. According to a recent nationwide study in Finland, the most common factors in first pregnancy associated with FOC in subsequent pregnancies were instrumental vaginal deliveries, in‐labor CS, third‐ or fourth‐degree tear of the perineum, and shoulder dystocia 7 . All of these factors might increase the intensity of the pain and therefore increase the desire for pain relief in subsequent pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent nationwide study in Finland, the most common factors in first pregnancy associated with FOC in subsequent pregnancies were instrumental vaginal deliveries, in-labor CS, third-or fourth-degree tear of the perineum, and shoulder dystocia. 7 All of these factors might increase the TA B L E 1 Background information on patients with diagnosed fear of childbirth and without diagnosed fear of childbirth who started labor in Finland from 2004 to 2018. a intensity of the pain and therefore increase the desire for pain relief in subsequent pregnancies. Confounding factors, such as higher body mass index among women with FOC might partly explain the higher rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have revealed that psychosocial factors, such as anxiety, neuroticism, depression, low self-esteem, and lack of social support, also play an important role in the development of FOC [3] . According to a recent case-control analysis in Finland, the main risk factors for the development of FOC in the second pregnancy were a previous fear of childbirth, unplanned cesarean section (CS), vacuum delivery, perineal tear, or shoulder dystocia [4] . Also, women with diagnosed FOC have been found to have a lower birth rate after the first pregnancy [5] .…”
Section: Introductionmentioning
confidence: 99%